2021
DOI: 10.1016/j.jvoice.2020.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Intraglottal Pressure Induced by Flow Separation Vortices Using Large Eddy Simulation

Abstract: The greatest rate of change in the glottal flow rate during phonation is a rapid decrease that occurs during the latter part of the glottal closing. Previous works showed that intraglottal flow separation vortices (FSVs) form in a divergent glottis, produce negative gauge pressures (below atmospheric) during closing. It is hypothesized here that FSVs contribute to the rapid closing mechanism of the true vocal folds during phonation.Four idealized static models (M5) of the human larynx were investigated using l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Regarding the vocal fold shape, most studies used the so-called "M5 model geometry" shown in Figure 2 which was first introduced as experimental static model by Scherer et al [13]. Although not officially defined as benchmark model, the M5 model became widely accepted for experimental and computational studies including static [14][15][16][17][18][19][20] as well as vibrating vocal folds of all types, i.e. driven dynamics [21][22][23][24][25][26][27][28][29][30].…”
Section: Vocal Fold Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the vocal fold shape, most studies used the so-called "M5 model geometry" shown in Figure 2 which was first introduced as experimental static model by Scherer et al [13]. Although not officially defined as benchmark model, the M5 model became widely accepted for experimental and computational studies including static [14][15][16][17][18][19][20] as well as vibrating vocal folds of all types, i.e. driven dynamics [21][22][23][24][25][26][27][28][29][30].…”
Section: Vocal Fold Modelsmentioning
confidence: 99%
“…Thus, several computational studies investigated the flow through static vocal folds at different instances during the oscillation cycle represented by different convergent or divergent transglottal shapes of the coronal glottal duct [14-17, 19, 20]. Most of these models are quasi-2D with a uniform rectangular glottis and without ventricular folds and vocal tract except the model by de Luzan et al [20] who performed simulations with 3D M5 models with uniform or divergent glottal duct. Beside the M5 model, other customized and/or physiologically based model types [11,31] as well as those with a much simpler geometry of the vocal folds as e.g.…”
Section: Vocal Fold Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Later experimental and computational studies also showed that the strength of FSV, and subsequently the negative pressure they augment, are proportional to the magnitude of the glottal divergent angle [3,8]. Farbos de Luzan et al [18] quantified the intraglottal negative pressure induced by FSV using large eddy simulation by comparing the pressure fields between a divergent channel and a straight channel. The geometric model is static but with a time-varying pressure waveform applied at the inlet of the domain.…”
Section: Introductionmentioning
confidence: 99%